Informational requirements of nudging - Jean-Michel Benkert; Nick Netzer (University of Zurich, Department of Economics, 2016)
A nudge is a paternalistic government intervention that attempts to improve choices by changing the framing of a decision problem. We propose a welfare-theoretic foundation for nudging similar in spirit to the classical revealed preference approach, by investigating a model where preferences and mistakes of an agent can be elicited from her choices under different frames. We provide characterizations of the classes of behavioral models for which nudging is possible or impossible, and we derive results on the required quantity of information.
Keywords: D03; D04; D60; D82; 330; nudge; framing; behavioral welfare economics; revealed preference